2009
DOI: 10.1097/brs.0b013e3181a19e66
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for the Outcome of Fusion in Adult Isthmic Spondylolisthesis

Abstract: The present study shows that patients working before surgery have a more favorable outcome. Also male gender and regular exercise are indicators of a better outcome after fusion. Female patients not working, not exercising or, if these factors are not known, with nonorganic PDs, should be informed about their suboptimal chances of an excellent outcome after fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 27 publications
6
60
0
1
Order By: Relevance
“…Similarly, patients who were still fully capable of working preoperatively may have stronger coping abilities and better social resources, allowing for fast and thorough rehabilitation. This finding is supported by Ekman et al, 8 who found working status to be the strongest predictor of a positive outcome.…”
Section: Socio-demographic Factorssupporting
confidence: 80%
“…Similarly, patients who were still fully capable of working preoperatively may have stronger coping abilities and better social resources, allowing for fast and thorough rehabilitation. This finding is supported by Ekman et al, 8 who found working status to be the strongest predictor of a positive outcome.…”
Section: Socio-demographic Factorssupporting
confidence: 80%
“…In previous outcome prediction studies specific for lumbar fusion patients, 25-30% of the variance in postsurgical ODI and pain VAS have been reported to be explained by regression models [9,41]. In our study, the models significantly explained 41.6, 36.0 and 25.6% of the variance in the 2-3 year measures of ODI, back pain VAS and EQ-5D, respectively.…”
Section: Discussionsupporting
confidence: 66%
“…Many possible reasons for mixed lumbar fusion surgery outcomes exist, including instrumentation failure, inadequate surgical technique and poor patient selection. Factors previously suggested to be predictive of pain and disability-related outcomes include pre-surgical pain/function [42], negative personality traits [19,31,40,41,44], emotional status [41], anxiety/depression [3,23,28,40,41], fear avoidance (FA) beliefs [28], negative outcome expectations [20,48] negative coping [3], smoking status [41], gender [9], exercise [9], litigation [23], duration of back pain and workers' compensation [3,19,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Data obtained from outcome studies do not support 1 method over another and each technique has its associated complications. 28,[42][43][44][45][46][47][48][49][50] Most of the published literature is retrospective with no standardization of either outcome measures or process measures. 43,51 The limited outcome studies suggest that a solid fusion, regardless of the technique or the approach, is important for successful patient outcomes.…”
Section: Discussionmentioning
confidence: 99%